Komunikasi Pemasaran, Kualitas Produk, dan Harga Terhadap Keputusan Pembelian - Tarigan, Purnaya Sari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
-Abstract This study aims to examine the influence of marketing communication, product quality, and price on purchase decisions among millennial Shopee users in Medan. The research targets all millennials who use Shopee within the city. Data were collected through an online questionnaire distributed to 100 qualified respondents who met the age and shopping experience criteria. Multiple linear regression analysis was employed to interpret the data. The results indicate that marketing communication and price exert a positive and significant effect on purchase decisions, while product quality demonstrates a positive but insignificant impact. The Adjusted R Square value of 41.7% suggests that the model explains a substantial portion of the variation in purchase decisions. Collectively, marketing communication, product quality, and price significantly influence purchase decisions among millennial Shopee users in Medan